Supramolecular ionic liquid gel electrolyte of solid-state zinc-iodine battery for high-voltage platform
By using supramolecular ionic liquid gel electrolyte in zinc ion batteries, using the supramolecular solvent exchange characteristics of polyvinyl alcohol network and ionic liquid, a stable ionic liquid gel was constructed, and the zinc ionic battery electrolyte in the existing technology was solved at high voltage in the existing technology The lack of performance on the platform has achieved higher cycle stability and application prospects.
Patent Information
- Application Number
- CN202411524294.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, the chemical stability, mechanical properties and electrochemical properties of zinc ion batteries on high voltage platforms are relatively poor, which limits the cyclic stability and application prospects of zinc ion batteries.
Using a supramolecular ionic liquid gel electrolyte, including ionic liquids prepared from 1-butyl-3-methylimidazole bromine salt and zinc bromide and hydrocoagulation prepared from zinc bromide, ultrapure water and polyvinyl alcohol The gel solution constructs a stable ionic liquid gel through non-coordination bonds, and uses the supramolecular solvent exchange characteristics of the polyvinyl alcohol network and the ionic liquid to form a self-supported solid electrolyte network.
It improves the chemical stability, mechanical properties and electrochemical properties of zinc ion batteries, extends the cycle life, improves the volume energy density, and achieves higher theoretical capacity and operating voltage.
Smart Images

Figure CN119400978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery on a high voltage platform. Background Art
[0002] Zinc metal has the characteristics of large theoretical capacity, low redox potential and abundant resources. The aqueous zinc-ion batteries prepared with it also have the advantages of high safety, low cost, environmental friendliness and high rate performance. Therefore, aqueous zinc-ion batteries have great application potential and research significance. Combined with the shortcomings of current commercial lithium-ion batteries such as poor safety and high hardness, they are not suitable for use in flexible devices. Therefore, it is necessary to develop solid-state batteries with high safety, excellent mechanical properties and excellent electrochemical performance and apply them to wearable fitness monitoring systems, artificial electronic skin, flexible electronic screens and other fields. However, during the charging process of zinc-ion batteries, the potential of hydrogen evolution is similar to the deposition potential of zinc, and hydrogen evolution reaction and a series of side reactions inevitably occur, which seriously limits the cycle life of aqueous zinc-ion batteries. In view of a series of problems of zinc metal negative electrodes during operation, the common solutions in the existing technical solutions include the design of new electrodes, optimization and modification of electrolytes, and modification of solid electrolytes and diaphragms.
[0003] The latest research results also announced a new solution, which is to use polymer electrolytes in batteries. Polymer electrolytes not only combine the advantages of both electrolyte modification and diaphragm modification methods, and make certain changes to the electrolyte composition and function, but also replace the diaphragm and directly become the medium between the positive and negative electrodes. This is because polymer electrolytes use polymers to construct a three-dimensional network, and there are active sites on their molecular chains that can interact with ions. There are also ions and solvents that transmit charge between the molecular chains, and the transmission mechanism of zinc ions is different from that of aqueous electrolytes. Therefore, polymer electrolytes can not only regulate the deposition behavior of zinc to inhibit the growth of dendrites, but also limit the activity of water molecules to inhibit the hydrogen evolution reaction. In addition, it has similar physical properties to the diaphragm, so it can replace the diaphragm to play the same role, thereby improving the zinc-ion battery to have a higher volume energy density. For example, a quasi-solid-state zinc-ion battery is prepared by forming a uniform zinc ion migration channel between the helical gelatin chains in the thermoreversible hydrogel electrolyte through the bridging effect of sulfate groups; this method successfully constructs a conformal electrode-electrolyte interface without an interfacial gap, guides the uniform deposition of zinc ions, and inhibits water-related side reactions through the gelation effect. However, its coulombic efficiency is not high enough, which leads to its mediocre performance in the full battery, and the long-cycle stability of the full battery is somewhat limited.
[0004] Judging from the above research results and the current processes, there is still much room for improvement in the use of polymers to prepare electrolytes for zinc-ion batteries. While considering the cycle stability, it is also necessary to consider its compatibility with the positive electrode material.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries on a high voltage platform. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery on a high voltage platform, so as to solve the problem of poor chemical stability, mechanical properties and electrochemical properties of the ionic liquid gel electrolyte in the prior art.
[0007] Based on the above objectives, the present invention provides a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery on a high voltage platform.
[0008] A supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery on a high voltage platform, characterized in that it comprises an ionic liquid and a hydrogel solution;
[0009] The ionic liquid is prepared from 1-butyl-3-methylimidazolium bromide and zinc bromide;
[0010] The hydrogel solution is prepared from zinc bromide, ultrapure water and polyvinyl alcohol.
[0011] Preferably, the preparation method of the ionic solution is as follows:
[0012] Zinc bromide is added to 1-butyl-3-methylimidazolium bromide, and then the mixture is stirred at 75-77° C. for 24-25 hours to obtain an ionic liquid.
[0013] Preferably, the usage ratio of 1-butyl-3-methylimidazolium bromide to zinc bromide is 50-55:51.3-56.4.
[0014] Preferably, the preparation method of the hydrogel solution is as follows:
[0015] Step A1. dissolving anhydrous zinc bromide in ultrapure water to obtain a zinc bromide solution;
[0016] Step A2. Add polyvinyl alcohol to the zinc bromide solution, and then stir evenly at 85-90° C. to obtain a hydrogel solution.
[0017] Preferably, the mass ratio of zinc bromide to ultrapure water in step A1 is 112.6-135.1:100-120.
[0018] Preferably, the usage ratio of the zinc bromide solution and polyvinyl alcohol in step A2 is 100 mL: 11.2-11.5 g.
[0019] Preferably, the preparation method of the supramolecular ionic liquid gel electrolyte is as follows:
[0020] The hydrogel solution is dripped into an electrolyte mold, and after drying, it is immersed in an ionic liquid to obtain a supramolecular ionic liquid gel electrolyte.
[0021] Preferably, the temperature during drying is 40-45°C.
[0022] Preferably, the soaking temperature is 28-30°C and the soaking time is 60-65h.
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high-voltage platform. The present invention utilizes the supramolecular solvent exchange characteristics of the ionic liquid to introduce a multifunctional ionic liquid into a polyvinyl alcohol network, and constructs a stable ionic liquid gel through non-coordination bonds, so that the gel electrolyte not only has excellent physical properties, but also can resist a certain external force to avoid deformation, thereby forming a self-supporting solid electrolyte network.
[0025] The present invention utilizes the Hofmeister effect to introduce a low concentration of zinc halide salt into the ionic liquid gel as an ion source for transferring charge, so that the ionic liquid gel electrolyte has the function of transferring zinc ions. The active sites on the polymer chain segments and the supramolecular effect of the ionic liquid jointly regulate the conduction of zinc ions, thereby achieving the stability of the zinc metal electrode interface and the cycle stability of the battery.
[0026] The ionic liquid gel electrolyte prepared by the present invention also contains a large amount of bromide ions that can catalyze the coupling of iodine, so that the positive valence conversion reaction of iodine ions occurs. The lower concentration of halide salt enables the zinc-iodine battery to exhibit a higher theoretical capacity and a higher operating voltage.
[0027] The ionic liquid added in the preparation process of the present invention also has a super solvent effect, which can reduce the water molecules in the network, and the polymer chain segment can also limit the activity of the water molecules, inhibiting the hydrogen evolution reaction while also preventing the product of the iodine positive valence conversion from being decomposed by water, thereby achieving high voltage and long cycle life of the zinc-iodine battery system;
[0028] The polyvinyl alcohol with a degree of polymerization of 170,000 to 220,000 is added to the hydrogel solution of the present invention, so that the ionic liquid gel also has good mechanical properties such as tensile stress and elongation at break;
[0029] Therefore, compared with the prior art, the supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries on a high voltage platform prepared by the present invention has better chemical stability, mechanical properties and electrochemical properties and a wider application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 Schematic diagram of the preparation process of the supramolecular ionic liquid gel electrolyte of the present invention;
[0032] Figure 2 The hydrogen nuclear magnetic resonance spectra of the supramolecular ionic liquid gel electrolyte and polyvinyl alcohol prepared in Example 1 and Comparative Example 1 of the present invention;
[0033] Figure 3 Fourier infrared spectra of the ionic liquid 1 and the supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention and the ionic liquid 2 and the supramolecular ionic liquid gel electrolyte prepared in Comparative Example 1 of the present invention;
[0034] Figure 4 After the supramolecular ionic liquid gel electrolyte prepared in Example 1 and Comparative Example 1 of the present invention was assembled into a zinc symmetric battery, the current density was 0.2 mA cm -2 Cycle curve diagram when
[0035] Figure 5 The supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention was assembled into a zinc symmetric battery at a current density of 0.1 mA cm -2 , deposition capacity is 0.1 mA cm -2 Scanning electron microscope photo of the metal negative electrode after 100 cycles of charge and discharge under the same conditions;
[0036] Figure 6 The coulombic efficiency and cycle number of the charge and discharge cycles of the supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention and Comparative Example 1 are assembled into a zinc-copper battery;
[0037] Figure 7 The supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention was assembled into a zinc-iodine battery and the -1 , 0.1Ag -1 , 0.2Ag -1 and 0.3Ag-1 Charge and discharge curves under current density;
[0038] Figure 8 After the supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention is assembled into a zinc-iodine battery, the -1 Capacity cycle relationship diagram under current density;
[0039] Fig. 9 This is a voltammogram of the supramolecular ionic liquid gel electrolyte prepared in Example 1 of the present invention assembled into a zinc-iodine battery at a scan rate of 0.2 mV / s. DETAILED DESCRIPTION
[0040] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0041] The sources and properties of some of the raw materials used in the present invention are as follows:
[0042] 1-Butyl-3-methylimidazolium bromide was purchased from Shandong Deke Biotechnology Co., Ltd., CAS: 85100-77-2; zinc bromide was purchased from Weifang Luze New Materials Co., Ltd., CAS: 7699-45-8; ammonium persulfate was purchased from Jinan Jinhao Chemical Co., Ltd., CAS: 7727-54-0; polyvinyl alcohol was purchased from Shaanxi Shangping Pharmaceutical Excipients Co., Ltd., CAS: 9902-89-5, with a degree of polymerization of 170,000-220,000.
[0043] Example 1: A method for preparing a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high voltage platform is as follows:
[0044] S1. Add 51.3 g of zinc bromide to 50 g of 1-butyl-3-methylimidazolium bromide, and then stir at 75 ° C for 24 hours to obtain an ionic liquid;
[0045] S2. Dissolve 112.6 g of zinc bromide in 100 mL of ultrapure water to obtain a zinc bromide solution;
[0046] S3. Add 11.2 g of polyvinyl alcohol to 100 mL of zinc bromide solution, and then stir evenly at 85 ° C to obtain a hydrogel solution;
[0047] S4. The hydrogel solution was dripped into the electrolyte mold, dried at 40°C, and then immersed in the ionic liquid at 28°C. After immersion for 60 hours, a supramolecular ionic liquid gel electrolyte was obtained;
[0048] Example 2: A method for preparing a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high voltage platform is as follows:
[0049] S1. Add 52.5 g of zinc bromide to 52 g of 1-butyl-3-methylimidazolium bromide, and then stir at 76 ° C for 24.3 h to obtain an ionic liquid;
[0050] S2. Dissolve 124 g of zinc bromide in 107 mL of ultrapure water to obtain a zinc bromide solution;
[0051] S3. Add 11.3 g of polyvinyl alcohol to 100 mL of zinc bromide solution, and then stir evenly at 87° C. to obtain a hydrogel solution;
[0052] S4. The hydrogel solution was dripped into the electrolyte mold, dried at 42°C, and then immersed in the ionic liquid at 29°C. After soaking for 62 hours, a supramolecular ionic liquid gel electrolyte was obtained;
[0053] Example 3: A method for preparing a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high voltage platform is as follows:
[0054] S1. Add 54.5 g of zinc bromide to 54 g of 1-butyl-3-methylimidazolium bromide, and then stir at 76 ° C for 24.7 h to obtain an ionic liquid;
[0055] S2. Dissolve 128 g of zinc bromide in 112 mL of ultrapure water to obtain a zinc bromide solution;
[0056] S3. Add 11.4 g of polyvinyl alcohol to 100 mL of zinc bromide solution, and then stir evenly at 89° C. to obtain a hydrogel solution;
[0057] S4. The hydrogel solution was dripped into the electrolyte mold, dried at 44°C, and then immersed in the ionic liquid at 29°C. After soaking for 64 hours, a supramolecular ionic liquid gel electrolyte was obtained;
[0058] Example 4: A method for preparing a supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high voltage platform is as follows:
[0059] S1. Add 56.4 g of zinc bromide to 55 g of 1-butyl-3-methylimidazolium bromide, and then stir at 77 ° C for 25 h to obtain an ionic liquid;
[0060] S2. Dissolve 135 g of zinc bromide in 120 mL of ultrapure water to obtain a zinc bromide solution;
[0061] S3. Add 11.5 g of polyvinyl alcohol to 100 mL of zinc bromide solution, and then stir evenly at 90 ° C to obtain a hydrogel solution;
[0062] S4. The hydrogel solution was dripped into the electrolyte mold, dried at 45°C, and then immersed in the ionic liquid at 30°C. After soaking for 65 hours, a supramolecular ionic liquid gel electrolyte was obtained;
[0063] Comparative Example 1:
[0064] Compared with Example 1, this comparative example only replaces "zinc bromide" with "zinc chloride", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a supramolecular ionic liquid gel electrolyte is obtained;
[0065] Comparative Example 2:
[0066] Compared with Example 1, this comparative example only replaces "51.3 g of zinc bromide" with "102.58 g of zinc bromide", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a supramolecular ionic liquid gel electrolyte is obtained;
[0067] Comparative Example 3:
[0068] Compared with Example 1, the "51.3 g of zinc bromide" added in the preparation process of the ionic liquid is replaced by "102.58 g of zinc bromide", and the "112.6 g of zinc bromide" added in the preparation process of the zinc bromide solution is replaced by "22.52 g of zinc bromide". The remaining steps and parameters are the same, and will not be repeated in this comparative example, and finally a supramolecular ionic liquid gel electrolyte is obtained.
[0069] Performance testing and data analysis:
[0070] The supramolecular ionic liquid gel electrolytes prepared in the above Examples 1 to 4 and Comparative Examples 1 to 3 were assembled into zinc metal symmetric batteries, and then the charging and discharging performance was tested. The test results are shown in Table 1:
[0071] Table 1
[0072] project Cycle life / h Example 1 1250 Example 2 1247 Example 3 1256 Example 4 1252 Comparative Example 1 1174 Comparative Example 2 600 Comparative Example 3 350
[0073] As shown in Table 1, the configuration ratio of 1-butyl-3-methylimidazolium bromide and zinc bromide in the ionic liquid and the concentration of the zinc bromide solution will affect the cycle life of the supramolecular ionic liquid gel electrolyte. By comparison, it can be seen that the supramolecular ionic liquid gel electrolyte prepared in the embodiment has the best performance;
[0074] The ionic conductivity of the supramolecular ionic liquid gel electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested, and the results obtained after calculation are shown in Table 2:
[0075] Table 2
[0076] project <![CDATA[Ionic conductivity / mS·cm -1 > Example 1 0.739 Example 2 0.732 Example 3 0.741 Example 4 0.734 Comparative Example 1 0.092 Comparative Example 2 0.698 Comparative Example 3 0.657
[0077] As can be seen from Table 2, the ionic conductivity of the supramolecular ionic liquid gel electrolyte prepared in the embodiment is higher, indicating that the embodiment can better promote the transmission of zinc ions and has better ion conductivity;
[0078] The supramolecular ionic liquid gel electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were made into a dumbbell shape of 50 mm × 4 mm × 2 mm, and then fixed on a sample holder of a universal test tensile machine (Shenzhen Sansi Metrology Co., Ltd., CMT-6000), and a tensile test was performed along the longitudinal axis. The results obtained after calculation are shown in Table 3:
[0079] Table 3
[0080] project Tensile stress / kPa Elongation at break / % Example 1 2300 1210 Example 2 2473 1272 Example 3 2386 1315 Example 4 2397 1286 Comparative Example 1 1100 1350 Comparative Example 2 2079 1231 Comparative Example 3 1776 1200
[0081] As can be seen from Table 3, although the elongation at break of the embodiment and the comparative example are similar, the stress generated when stretched to similar multiples is quite different. It takes a larger external force to pull the embodiment to the limit, indicating that the embodiment has better physical properties and is more advantageous in resisting stress.
[0082] The nuclear magnetic resonance hydrogen spectra of the supramolecular ionic liquid gel electrolyte and polyvinyl alcohol prepared in Example 1 and Comparative Example 1 were measured. Figure 2 ,from Figure 2 It can be seen that the peak signals of the hydroxyl groups in Example 1 and Comparative Example 1 and the peak signals of the imidazolium hydrogen ions in the ionic liquid are offset, which may be due to the interaction between the prepared ionic liquid and the hydroxyl groups of the polyvinyl alcohol;
[0083] The Fourier transform infrared spectra of the ionic liquid 1 and the supramolecular ionic liquid gel electrolyte prepared in Example 1 and the ionic liquid 2 and the supramolecular ionic liquid gel electrolyte prepared in Comparative Example 1 of the present invention were measured to obtain Figure 3 ,analyze Figure 3 It can be seen that the ionic liquid forms an ionic liquid gel with polyvinyl alcohol, but the ionic liquid gel prepared in Example 1 has relatively better performance;
[0084] After the supramolecular ionic liquid gel electrolyte prepared in Example 1 and Comparative Example 1 was assembled into a zinc symmetric battery, the current density was 0.2 mA cm -2 The measured cycle curve is obtained Figure 4 ,analyze Figure 4 It can be seen that Example 1 has a more stable ion-conducting ability and a longer cycle life;
[0085] After the supramolecular ionic liquid gel electrolyte prepared in Example 1 was assembled into a zinc symmetric battery, the current density was 0.1 mA cm -2 , deposition capacity is 0.1mAcm -2After 100 cycles of charge and discharge under the same conditions, the metal negative electrode was scanned by scanning electron microscopy and the Figure 5 ,from Figure 5 It can be seen that the zinc metal deposition on the surface of the zinc negative electrode is uniform, and there is no significant dendrite growth;
[0086] The supramolecular ionic liquid gel electrolyte prepared in Example 1 and Comparative Example 1 was assembled into a zinc-copper battery, and the relationship between the coulombic efficiency and the number of cycles of the charge and discharge cycle was analyzed to obtain Figure 6 ,analyze Figure 6 It can be seen that the cycle performance of the zinc-copper battery system in the embodiment is more stable;
[0087] The supramolecular ionic liquid gel electrolyte prepared in Example 1 was assembled into a zinc-iodine battery. -1 , 0.1Ag -1 , 0.2Ag -1 and 0.3Ag -1 After the charge and discharge test at the current density Figure 7 ,from Figure 7 It can be seen that its charge-discharge curves have voltage platforms at 1.2V and 1.4V, indicating that the electrolyte successfully stimulates the positive valence conversion of iodine;
[0088] The supramolecular ionic liquid gel electrolyte prepared in Example 1 was assembled into a zinc-iodine battery. -1 After testing under current density and analyzing the relationship between the capacity and number of cycles, we can get Figure 8 ,from Figure 8 It can be seen that the embodiment is applied to zinc-iodine batteries, showing excellent cycle stability and long cycle life;
[0089] The supramolecular ionic liquid gel electrolyte prepared in Example 1 was assembled into a zinc-iodine battery and scanned at 0.2 mV / s to obtain a voltammetric curve. Fig. 9 ,from Fig. 9 It can be seen that the embodiment has good electrochemical stability.
[0090] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0091] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A supramolecular ionic liquid gel electrolyte for a solid-state zinc-iodine battery for a high voltage platform, characterized in that: including ionic liquid and hydrogel solutions; The ionic liquid is prepared from 1-butyl-3-methylimidazolium bromide and zinc bromide; The hydrogel solution is prepared from zinc bromide, ultrapure water and polyvinyl alcohol.
2. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 1, characterized in that: The preparation method of the ionic solution is as follows: Zinc bromide is added to 1-butyl-3-methylimidazolium bromide, and then the mixture is stirred at 75-77° C. for 24-25 hours to obtain an ionic liquid.
3. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 2, characterized in that: The dosage ratio of the 1-butyl-3-methylimidazolium bromide to zinc bromide is 50-55:51.3-56.
4.
4. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 1, characterized in that: The preparation method of the hydrogel solution is as follows: Step A1. dissolving anhydrous zinc bromide in ultrapure water to obtain a zinc bromide solution; Step A2. Add polyvinyl alcohol to the zinc bromide solution, and then stir evenly at 85-90° C. to obtain a hydrogel solution.
5. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 4, characterized in that: The mass ratio of zinc bromide to ultrapure water in step A1 is 112.6-135.1:100-120.
6. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 4, characterized in that: The usage ratio of the zinc bromide solution and polyvinyl alcohol in step A2 is 100 mL: 11.2-11.5 g.
7. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 1, characterized in that: The preparation method of the supramolecular ionic liquid gel electrolyte is as follows: The hydrogel solution is dripped into an electrolyte mold, and after drying, it is immersed in an ionic liquid to obtain a supramolecular ionic liquid gel electrolyte.
8. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 7, characterized in that: The temperature during the drying is 40-45°C.
9. The supramolecular ionic liquid gel electrolyte for solid-state zinc-iodine batteries for high voltage platforms according to claim 7, characterized in that: The soaking temperature is 28-30° C. and the soaking time is 60-65 hours.
Citation Information
Patent Citations
Gel electrolyte and zinc-bromine or zinc-iodine single flow battery
CN113036156A
Additive of aqueous battery electrolyte and application thereof
CN115149117A
Electrolyte of local high-concentration ionic liquid, preparation method of electrolyte and assembled high-voltage zinc tellurium battery
CN118738599A
Zinc secondary battery
JP2020161308A
Metal ion coordinated chitosan electrolyte for ion transport, its structure and fabrication method
US20240021875A1
Cited By
Zinc-iodine battery based on zinc bromide electrolyte
CN119601673A